Assessing international trade in healthcare services - Lior Herman (European Centre for International Political Economy (ECIPE), 2009)
Growing evidence indicates that international trade in healthcare services is growing. Nevertheless, a major literature gap exists with regard to the nature of international healthcare trade and its extent. Taking a comprehensive approach, this research examines the magnitude, directions, patterns of specialisation, growth and other aspects related to international trade in healthcare services. Within this framework, trade is analysed with regard to cross border trade, consumption of healthcare by foreign nationals, commercial presence of healthcare services providers, as well as the movement of healthcare professionals across borders.
Keywords: F14; F15; F20; F22; F23; I11; 330; healthcare services; international trade; modes of supply; cross border trade; consumption abroad; commercial presence; movement of natural persons